Microcrystalline cellulose from biomass-palm oil frond - Mohamad Salihi, Ramli (2015)
Malaysia, being the world's largest producer and exporter of palm oil, is currently producing about 47% of the world's supply and Indonesia is second, producing approximately 36% of world palm oil capacity. Both nations are expanding their palm oil production capacity and the market continues to grow. With the current acreage of 4.49 million hectares of Palm Oil Cultivation in Malaysia, it is estimate 26.2 million tonnes of oil palm frond are treated as biomass. Oil palm frond consist huge amount of fiber, in which it can be transform into cellulose. Fronds are taken from oil palm tree as wastes, which are normally burnt. This research is to prepare and produce the cellulose fiber from oil palm frond. Steam explosion pre-treatment was conducted to enhance the accessibility of the oil palm frond lignocellulose. The combination of temperature and time known as the Log Ro in steam explosion process were used as the main parameter in this research. It has many applications in pharmaceuticals, nutraceuticals, foods, paper and structural composites. For pharmaceutical uses, it is used as a binding agent and also as a disintegrating agent. MCC also naturally derived stabilizer, texturing agent and a fat substitute. The MCC was prepared by controlled acid hydrolysis of the isolated α-cellulose which attacked the amorphous region and was followed by the back neutralization process alkalization. The structural properties of cellulose and microcrystalline cellulose (MCC) were studied by Scanning Electron Microscope (SEM). Basically the process for producing microcrystalline cellulose (MCC) involves preparation of holocellulose and α-cellulose from oil palm frond. The steam explosion method was used to prepare holocellulose and a few parameters are involved which is pressure, temperature, retention time and severity of structural cell wall. By control the pressure it will automatically change the others parameters. The pressure is 5 bars, 10 bars and 20 bars were used and the result of the severity of structural cell was analyzed.